A ideia de Revolução Científica na obra de John Desmond Bernal - Oliveira, Luís Henrique São João (2017)
This dissertation focuses on the idea of Scientific Revolution according to John Desmond Bernal (1901-1971), remarkable British scientist who started the studies about science based on Marxist concepts. The first chapter is about the existence of multiple possibilities for historical approaches about the Scientific Revolution, as well as the concepts Bernal came up with and how it is stablished within his own time, the 1950’s and 1960’s. The second chapter focuses on the production of Bernal’s theory, his view of science in a time when the discussions about which role should the State play in the society, and the social responsibilities of the institutions. It also discusses Bernal’s perspectives and role at that historical moment, from his defense of the Soviet Union as the ideal social model for the development of science and Marxism as a way to understand science itself. It is also about how his beliefs brought up a great debate with intellectuals and scientists of that time with many divergent political beliefs concerning the role science should play, and from which standpoint it should be put into practice. The third chapter is about the concept of Scientific Revolution found in Science in History and how it is connected to the ideas of production according to Marx’s theory. The first part of this chapter analyses the importance Bernal gives to Marx’s idea of production to develop his own studies about history of science. The second part addresses the way Bernal tried to bring a new meaning to the Scientific Revolution, as a special moment in which the natural sciences are no longer determined just by social production, but also seen as a fundamental productive power to make social changes possible